Konsepsi Madrasah dan Perkembangannya dalam Inovasi Pengetahuan serta Pasang Surutnya - Ikmal, Happy (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
In the early days of the development of Islam, of course, systematic formal education had not been established. The ongoing education can be said to be informal; and this is also more related to the efforts of Islamic da'wah to spread and plant the basics of Islamic belief and worship. In this connection it is understandable why the process of Islamic education first occurred at the home of a certain friend of the Prophet SAW; the most famous is Dar al-Arqam. However, when the Islamic community was formed, education was held in the mosque. The educational process in both places is carried out in the learning circle. Every time Islam is introduced to any place, it is always introduced along with religious education while at the same time Arabic is always the medium of its teaching. That is why the desire to study Islam and its lingua-franca (Arabic) is always very high among Muslims. This also explains the nature of Arabic and Islamic studies which are inseparable as twin courses which are always in line with each other. The results of empirical investigations understand the character of Muslim subjectivity finding the most useful Qur'anic reading, because they discover how the vision of dynamic education and transformative pedagogy defines the content, composition and communication style of Islamic Divine discourse. This brought various scientific innovations and produced Islamic inventors from madrasas, but after the sixteenth century, the madrasa curriculum became trapped in traditional Islamic sciences, there was a close connection to this fact and the decline of the Ottoman Empire, on occasions that different. the effect of the Mongol invasion of the Muslim world that weakened the spirit of Muslims. the Muslim world collapsed and stagnated. Apart from the two things above, Often, innovative new approaches are dismissed as attempts to damage or damage Muslim discursive traditions or worse, are considered conspiracies hatched by Orientalists and carried out by Muslim clerics who are deceitful and fickle